Solid-state battery and preparation method thereof

By using a composite solid electrolyte membrane in the solid-state battery of lithium-ion batteries and using oxide solid electrolyte as active filler, the problems of thermal runaway battery cells and lithium dendrites in the battery are solved, and the ionic conductivity and electrochemical window are improved.

CN119695255APending Publication Date: 2025-03-25JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411612974.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems with thermal runaway from the battery cell. The flammable and explosive organic carbonate solvents in liquid electrolytes are one of the main inducing factors of thermal runaway, and the ionic conductivity and lithium dendrites of solid electrolytes in solid batteries have not been effectively solved.

Method used

A composite solid electrolyte membrane is adopted, including a first solid electrolyte layer close to the positive electrode and a second solid electrolyte layer close to the negative electrode. By adding an oxide solid electrolyte as an active filler to the polymer electrolyte, the degree of crystallization of the polymer is reduced, the amorphous region is increased, the ionic conductivity is improved, and the problem of lithium dendrites is alleviated.

Benefits of technology

It improves the ionic conductivity of solid-state batteries, alleviates safety problems such as short circuits caused by lithium dendrites, and broadens the electrochemical window to adapt to battery operation under high and low voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695255A_ABST
    Figure CN119695255A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a solid-state battery and a preparation method thereof. The solid-state battery comprises a positive electrode, a negative electrode and a composite solid-state electrolyte membrane positioned between the positive electrode and the negative electrode, the composite solid electrolyte membrane comprises a first solid electrolyte layer and a second solid electrolyte layer, the first solid electrolyte layer is close to the positive electrode, and the second solid electrolyte layer is close to the negative electrode; the first solid electrolyte layer comprises a first composite polymer electrolyte, the first composite polymer electrolyte comprises a first polymer solid electrolyte and a first active filler, and the first active filler comprises a first oxide solid electrolyte; the second solid electrolyte layer comprises a second composite polymer electrolyte, the second composite polymer electrolyte comprises a second polymer solid electrolyte and a second active filler, and the second active filler comprises a second oxide solid electrolyte. According to the invention, the ionic conductivity can be improved, the electrochemical window is widened, the problem of lithium dendrites is relieved, and the cycle performance and safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a solid-state battery and a method for preparing the same. Background Art

[0002] The safety of lithium-ion batteries is one of the top priorities in the current development of lithium-ion batteries. Under electrical abuse, thermal abuse, and mechanical abuse, lithium-ion batteries are very prone to thermal runaway, and the flammable and explosive organic carbonate solvents in the liquid electrolyte are considered to be one of the main factors causing thermal runaway. At present, the solution to the thermal runaway problem of liquid batteries is to optimize the electrochemical system of the battery to suppress the possibility of thermal runaway, such as controlling the peak temperature and the temperature rise rate, but these are all auxiliary improvements for the thermal runaway of the battery, and do not fundamentally improve and prevent the thermal runaway of the battery. In addition, in order to solve the thermal runaway problem of lithium batteries, inert materials are coated on the surface of the positive and negative electrode materials to solve the short circuit of the positive and negative electrodes caused by the shrinkage of the diaphragm when the temperature rises. The coating of related substances on the diaphragm is also based on such considerations; in addition, flame retardants are added to the battery to prevent the burning of materials when thermal runaway occurs.

[0003] Solid-state batteries are currently considered to be one of the more effective ways to solve thermal runaway of battery cells. There is no flowing flammable electrolyte inside the all-solid-state battery, which can effectively avoid combustion caused by organic solvents, and the solid electrolyte has a high shear modulus, which can prevent the growth of lithium dendrites.

[0004] Among solid electrolytes, polymer solid electrolytes have been widely used due to their good solid-solid contact and high overlap with existing processes. However, the electrochemical window of single polymer electrolytes is small, and they are easily oxidized under high voltage and easily reduced under low voltage. Therefore, it is necessary to find a polymer system that can adapt to high and low voltage. In addition, the solid electrolytes in existing solid-state batteries still have problems such as ion conductivity that needs to be improved, and the problem of lithium dendrite growth that needs to be further alleviated.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a solid-state battery and a preparation method thereof, which can improve the ionic conductivity of the solid electrolyte membrane, alleviate the problem of lithium dendrite growth, and alleviate the problem of small electrochemical window of a single polymer electrolyte.

[0007] In order to solve the above technical problems, this application is implemented as follows:

[0008] According to one aspect of the present application, an embodiment of the present application provides a solid-state battery, the solid-state battery comprising a positive electrode, a negative electrode, and a composite solid electrolyte membrane located between the positive electrode and the negative electrode;

[0009] The composite solid electrolyte membrane includes a first solid electrolyte layer and a second solid electrolyte layer disposed on the surface of the first solid electrolyte layer, the first solid electrolyte layer is close to the positive electrode, and the second solid electrolyte layer is close to the negative electrode;

[0010] The first solid electrolyte layer includes a first composite polymer electrolyte, the first composite polymer electrolyte includes a first polymer solid electrolyte and a first active filler, and the first active filler includes a first oxide solid electrolyte;

[0011] The second solid electrolyte layer includes a second composite polymer electrolyte, the second composite polymer electrolyte includes a second polymer solid electrolyte and a second active filler, and the second active filler includes a second oxide solid electrolyte.

[0012] In addition, the solid-state battery according to the present application may also have the following additional technical features:

[0013] In some embodiments, the LUMO energy level of the first polymer solid electrolyte is lower than the LUMO energy level of the second polymer solid electrolyte.

[0014] In some embodiments, the LUMO energy level of the first oxide solid electrolyte is lower than the LUMO energy level of the second oxide solid electrolyte.

[0015] In some embodiments, the first oxide solid electrolyte includes at least one of LATP, LLZTO or LAGP.

[0016] In some embodiments, the second oxide solid electrolyte includes LLZO, LLTO, Li 2 O.B 2 O 3 , Li 2 O·LiI or Li 2 At least one of O·LiBr.

[0017] In some embodiments, the first polymer solid electrolyte includes a first polymer, a second polymer and a first lithium salt, and the second polymer solid electrolyte includes a third polymer and a second lithium salt; the first composite polymer electrolyte and the second composite polymer electrolyte satisfy at least one of the following characteristics (1) to (7): (1) the first polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyvinylidene fluoride, polyvinyl alcohol, polymethyl methacrylate, polyethylene terephthalate or polyimide; (2) the second polymer includes at least one of polyethylene glycol diacrylate, polyvinyl alcohol, polymethyl methacrylate, polyimide or poly(1,3-dioxolane), and the second polymer is of a different type from the first polymer; (3) the third polymer includes at least one of polymethyl methacrylate, polyethylene oxide, polyacrylonitrile or polyvinyl pyrrolidone, and the third polymer is of a different type from the first polymer and the second polymer; (4) the first lithium salt includes LiTFSI, LiPF 6 , LiBF 4 , LiBOB, LiFSI, LiODFB or LiNO 3 At least one of; (5) the second lithium salt includes LiTFSI, LiPF 6 , LiBF 4 , LiBOB, LiFSI, LiODFB or LiNO 3 At least one of the following: (6) The mass ratio of the first polymer, the second polymer, the first lithium salt, and the first oxide solid electrolyte is (20-30): (5-10): (20-30): (30-40). (7) The mass ratio of the third polymer, the second lithium salt, and the second oxide solid electrolyte is (20-35): (10-20): (40-60).

[0018] In some embodiments, the particle size of the first oxide solid electrolyte in the first composite polymer electrolyte presents a gradient distribution, and the particle size of the first oxide solid electrolyte presents a decreasing trend along the direction approaching the positive electrode.

[0019] In some embodiments, the concentration of the first oxide solid electrolyte in the first composite polymer electrolyte presents a gradient distribution, and the concentration of the first oxide solid electrolyte presents a decreasing trend along a direction approaching the positive electrode.

[0020] In some embodiments, the particle size of the second oxide solid electrolyte in the second composite polymer electrolyte presents a gradient distribution, and the particle size of the second oxide solid electrolyte presents an increasing trend along the direction approaching the negative electrode.

[0021] In some embodiments, the concentration of the second oxide solid electrolyte in the second composite polymer electrolyte presents a gradient distribution, and the concentration of the second oxide solid electrolyte presents an increasing trend along a direction approaching the negative electrode.

[0022] In some embodiments, the first solid electrolyte layer further includes a first plasticizer, the second solid electrolyte layer further includes a second plasticizer, and the first solid electrolyte layer and the second solid electrolyte layer satisfy at least one of the following characteristics (1) to (4): (1) the first plasticizer includes at least one of dimethyl carbonate, ethyl methyl carbonate or propylene carbonate; (2) the mass fraction of the first plasticizer in the first solid electrolyte layer is 1% to 2%; (3) the second plasticizer includes at least one of dimethyl carbonate, ethyl methyl carbonate or propylene carbonate; (4) the mass fraction of the second plasticizer in the second solid electrolyte layer is 1% to 2%.

[0023] In some embodiments, the thickness of the first solid electrolyte layer is A, the thickness of the second solid electrolyte layer is B, and A and B satisfy: 4 / 10≤A / (A+B)≤6 / 10.

[0024] In some of the embodiments, 5 μm≤A+B≤30 μm.

[0025] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a solid-state battery, which comprises the following steps:

[0026] S1, mixing a raw material for preparing a first polymer solid electrolyte and a first active filler to obtain a first mixed solution, and subjecting the first mixed solution to a cross-linking polymerization reaction to obtain a first solid electrolyte layer, wherein the first active filler includes a first oxide solid electrolyte;

[0027] S2, mixing a raw material for preparing a second polymer solid electrolyte and a second active filler to obtain a second mixed solution, subjecting the second mixed solution to an in-situ polymerization reaction to obtain a second solid electrolyte layer, wherein the second active filler includes a second oxide solid electrolyte;

[0028] S3, compounding the first solid electrolyte layer and the second solid electrolyte layer to obtain a composite solid electrolyte membrane;

[0029] S4. Place the composite solid electrolyte membrane between the positive electrode and the negative electrode, with the first solid electrolyte layer close to the positive electrode and the second solid electrolyte layer close to the negative electrode, to obtain a solid-state battery.

[0030] In some embodiments, in step S1, mixing the raw material for preparing the first polymer solid electrolyte and the first active filler comprises: firstly mixing the first polymer and the first solvent evenly, then adding the second polymer, the photoinitiator and the first lithium salt, mixing evenly to obtain a first intermediate mixed solution, mixing the first intermediate mixed solution with the first active filler to obtain the first mixed solution,

[0031] In some embodiments, in step S1, the cross-linking polymerization reaction is carried out under the action of a photoinitiator and under the irradiation of ultraviolet light.

[0032] In some embodiments, in step S2, mixing the raw materials for preparing the second polymer solid electrolyte and the second active filler includes: mixing the second active filler with a dispersant and a second solvent, and then adding a second lithium salt and a monomer for forming a third polymer to obtain the second mixed solution.

[0033] In some embodiments, the first solvent includes at least one of N,N-dimethylformamide, N-methylpyrrolidone or polyethylene glycol.

[0034] In some embodiments, the second solvent includes at least one of N,N-dimethylformamide, N-methylpyrrolidone or polyethylene glycol.

[0035] In some of the embodiments, the dispersant includes an alcohol.

[0036] In some embodiments, the second mixed solution further contains an initiator, and the initiator includes azobisisobutyronitrile.

[0037] In some embodiments, the intensity of the ultraviolet light is 220 mW / cm 2 Up to 230mW / cm 2 within the range.

[0038] In some embodiments, the conditions of the in-situ polymerization reaction include: a temperature of 70° C. to 100° C., a time of 20 min to 60 min, and a rotation speed of 300 r / min to 1000 r / min.

[0039] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0040] In the embodiment of the present application, in the solid-state battery provided, the composite solid electrolyte membrane includes a first solid electrolyte layer near the positive electrode and a second solid electrolyte layer near the negative electrode, the first solid electrolyte layer includes a first composite polymer electrolyte, the first composite polymer electrolyte includes a first polymer solid electrolyte and a first active filler, and the first active filler is a first oxide solid electrolyte; the second solid electrolyte layer includes a second composite polymer electrolyte, the second composite polymer electrolyte includes a second polymer solid electrolyte and a second active filler, and the second active filler is a second oxide solid electrolyte. Thus, in the first composite polymer electrolyte, the first oxide solid electrolyte is used as the first active filler, and in the second composite polymer electrolyte, the second oxide solid electrolyte is used as the second active filler, that is, by using the oxide solid electrolyte as the active filler, relying on the nanoparticle size and Lewis alkalinity of the oxide solid electrolyte to reduce the crystallinity of the polymer electrolyte, increase the amorphous region, increase the polymer dielectric constant, promote the solubility of lithium salts and the lithium ion migration coefficient, and at the same time cooperate with the solid electrolyte solid ion transmission and the liquid transmission of the plasticizer to further accelerate the ionic conductivity. Thus, by using the oxide solid electrolyte as the active filler, the glass transition temperature of the composite polymer electrolyte can be reduced and the ionic conductivity can be improved. In addition, by using oxide solid electrolytes as active fillers in polymer electrolytes, the lithium dendrite problem existing in oxide solid electrolytes in existing solid-state batteries can be alleviated, and safety issues such as short circuits caused by lithium dendrite growth can be effectively alleviated.

[0041] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Shown is a SEM schematic diagram of the composite solid electrolyte membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0046] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0047] Traditional liquid electrolyte batteries have poor safety issues. For example, the flammable and explosive organic carbonate solvents in existing liquid electrolytes are generally considered to be one of the main factors causing thermal runaway. In the related art, flame retardants are added to alleviate this problem. However, adding flame retardants to liquid batteries (conventional batteries) will aggravate side reactions, thicken the SEI film, and affect the battery cycle performance. In addition, too little flame retardant will not have a flame retardant effect, and too much addition will affect the battery energy density. In addition, conventional batteries currently use diaphragms, liquid electrolytes, and lithium salts dissolved therein. At high temperatures, carbonate electrolytes are unstable and easily cause thermal runaway. After the diaphragm shrinks, the first thing to burn is the liquid carbonate. Compared with traditional liquid electrolyte batteries, all-solid-state batteries have the characteristics of good safety. However, current solid-state batteries still have more or less shortcomings, such as: (1) Existing oxide solid electrolytes have solid-solid contact problems. The contact area between the oxide solid electrolyte and the electrode is too small, and there are grain boundary gaps in the oxide solid electrolyte. Lithium dendrites will grow along this gap, causing short circuit between the positive and negative electrodes and thus causing a short circuit; (2) Existing single polymer electrolytes have a small electrochemical window and are easily oxidized under high voltage and easily reduced under low voltage. It is necessary to find a polymer system that can adapt to high and low voltages; or, the existing single polymer solid electrolyte has low ionic conductivity and cannot meet the needs of power batteries. In addition, the electrochemical window of the single polymer solid electrolyte is too narrow. Since the LUMO energy level is too low, it is easy to be reduced at the negative electrode, and the HOMO energy level is too high, it is easy to be oxidized at high potential at the positive electrode, and the electrochemical uncertainty is poor.

[0048] In view of this, the inventors of this application have proposed a solid-state battery and a method for preparing a solid-state battery through extensive research, which can not only alleviate the problem of poor ionic conductivity of solid electrolytes in existing solid-state batteries, but also alleviate the problem of lithium dendrites in existing solid electrolytes and the problem of small electrochemical window of existing single polymer electrolytes. The specific technical solution is described below.

[0049] In a first aspect, in some embodiments, the present application provides a solid-state battery, comprising a positive electrode, a negative electrode, and a composite solid-state electrolyte membrane located between the positive electrode and the negative electrode; wherein the composite solid-state electrolyte membrane comprises a first solid-state electrolyte layer and a second solid-state electrolyte layer arranged on the surface of the first solid-state electrolyte layer, the first solid-state electrolyte layer is close to the positive electrode, and the second solid-state electrolyte layer is close to the negative electrode.

[0050] The composite solid electrolyte membrane provided by the present invention has a double-layer structure, that is, the composite solid electrolyte membrane comprises a stacked double-layer structure, the double-layer structure of the double-layer composite solid electrolyte membrane comprises a first solid electrolyte layer and a second solid electrolyte layer, and the second solid electrolyte layer can be arranged on one of the surfaces of the first solid electrolyte layer along the thickness direction.

[0051] The composite solid electrolyte membrane provided by the embodiment of the present invention can be applied to solid-state batteries, and can further be applied to all-solid-state batteries. When the composite solid electrolyte membrane of the present invention is applied to a solid-state battery, the first solid electrolyte layer can be arranged close to the positive electrode, and the second solid electrolyte layer can be arranged close to the negative electrode. That is, the composite solid electrolyte membrane includes a first solid electrolyte layer close to the positive electrode side and a second solid electrolyte layer close to the negative electrode side.

[0052] In some preferred embodiments, in the above-mentioned composite solid electrolyte membrane, the first solid electrolyte layer includes a first composite polymer electrolyte, the first composite polymer electrolyte includes a first polymer solid electrolyte and a first active filler, the first active filler includes a first oxide solid electrolyte; the second solid electrolyte layer includes a second composite polymer electrolyte, the second composite polymer electrolyte includes a second polymer solid electrolyte and a second active filler, the second active filler includes a second oxide solid electrolyte.

[0053] Optionally, the first oxide solid electrolyte and the second oxide solid electrolyte are of different specific types.

[0054] In the present application, the first composite polymer electrolyte in the first solid electrolyte layer is mainly composed of a first polymer electrolyte and a first active filler, and the second composite polymer electrolyte in the second solid electrolyte layer is mainly composed of a second polymer electrolyte and a second active filler, wherein the first active filler and the second active filler are respectively a first oxide solid electrolyte and a second oxide solid electrolyte, and preferably, the first oxide solid electrolyte and the second oxide solid electrolyte are different. Therefore, the present invention reduces the glass transition temperature of the polymer and improves the ionic conductivity by using active fillers, in detail:

[0055] In the first composite polymer electrolyte, the first oxide solid electrolyte is used as the first active filler, and in the second composite polymer electrolyte, the second oxide solid electrolyte is used as the second active filler. That is, the oxide solid electrolyte is used as the active filler, and the nanoparticle size and Lewis alkalinity of the oxide solid electrolyte are relied on to reduce the crystallinity of the polymer electrolyte, increase the amorphous region, increase the polymer dielectric constant, promote the solubility of lithium salts and the lithium ion migration coefficient, and at the same time, cooperate with the solid electrolyte solid ion transmission and the liquid transmission of the plasticizer to further accelerate the ion conductivity. Therefore, by using the oxide solid electrolyte as the active filler, the glass transition temperature of the composite polymer electrolyte can be reduced and the ion conductivity can be improved.

[0056] Moreover, compared with the prior art, the use of liquid electrolytes is very easy to produce lithium dendrites due to uneven deposition of lithium, piercing the diaphragm and causing thermal runaway problems. Alternatively, although the existing oxide solid electrolyte has an ultra-high shear modulus, when the oxide solid electrolyte is applied to the solid electrolyte layer, it will cause the growth of lithium dendrites due to the presence of spaces between particles and grain boundary gaps. The present invention not only has an ultra-high shear modulus, but also eliminates the space available for the growth of lithium dendrites by adding oxide solid electrolytes as active fillers in polymer solid electrolytes, and can basically completely isolate lithium dendrites from piercing the solid electrolyte layer. Thus, in the first composite polymer electrolyte, the first oxide solid electrolyte is used as the first active filler, and in the second composite polymer electrolyte, the second oxide solid electrolyte is used as the second active filler, that is, by using oxide solid electrolytes as active fillers in polymer electrolytes, the lithium dendrite problem existing in oxide solid electrolytes in existing solid-state batteries can be alleviated, and safety problems such as short circuits caused by the growth of lithium dendrites can be effectively alleviated.

[0057] Furthermore, compared with the problem of too narrow electrochemical window of existing single polymer solid electrolytes, the present invention adopts different oxide solid electrolytes in the first solid electrolyte layer close to the positive electrode side and the second solid electrolyte layer close to the negative electrode side, that is, different composite polymer electrolytes are formed, which can widen the electrochemical window, making it less likely to be reduced on the negative electrode side and less likely to be oxidized on the positive electrode side, thereby alleviating the problem that the existing single polymer solid electrolyte cannot meet the wide voltage window.

[0058] In some preferred embodiments, the first solid electrolyte layer and the second solid electrolyte layer of the present invention may also contain a plasticizer, which can play a role in strengthening the interface contact. Thus, the present invention uses a polymer plus active filler to reduce the glass transition temperature, increase the amorphous region, and increase the flexibility of the polymer, while adding a plasticizer, so that while ensuring mechanical strength, the flexibility of the material is increased to enhance the contact with the positive and negative electrodes and reduce the interface resistance.

[0059] In some embodiments, the LUMO energy level of the first polymer solid electrolyte is lower than the LUMO energy level of the second polymer solid electrolyte.

[0060] In some embodiments, the LUMO energy level of the first oxide solid state electrolyte is lower than the LUMO energy level of the second oxide solid state electrolyte.

[0061] It should be understood that LUMO is the lowest unoccupied orbital of a molecule. The lower the LUMO energy level, the easier it is for the substance to obtain electrons. For electrolytes, the LUMO energy level can be used to determine the order in which the components are oxidized or reduced during the charging process. The lower the LUMO energy level of the component, the easier it is to be reduced at low voltage.

[0062] Thus, the LUMO energy level of the raw material used to prepare the first polymer solid electrolyte is relatively low, and the LUMO energy level of the raw material used to prepare the second polymer solid electrolyte is relatively high, so that the LUMO energy level of the prepared first polymer solid electrolyte is lower than the LUMO energy level of the second polymer solid electrolyte. The LUMO energy level of the first oxide solid electrolyte used is relatively low, and the LUMO energy level of the second oxide solid electrolyte used is relatively high, so that the LUMO energy level of the first oxide solid electrolyte is lower than the LUMO energy level of the second oxide solid electrolyte. Furthermore, in the composite solid electrolyte membrane, in comparison, the first composite polymer electrolyte in the first solid electrolyte layer close to the positive electrode side is mainly prepared and formed using raw materials with a lower LUMO energy level, and the second composite polymer electrolyte in the second solid electrolyte layer close to the negative electrode side is mainly prepared and formed using raw materials with a higher LUMO energy level.

[0063] Compared with the solid electrolyte membrane with a single-layer structure, the present invention arranges the solid electrolyte into a double-layer structure with different LUMO energy levels, and arranges the second solid electrolyte layer with a higher LUMO energy level close to the negative electrode of the battery, and the first solid electrolyte layer with a lower LUMO energy level close to the positive electrode of the battery. In this way, by using a high LUMO energy band gap polymer in the second solid electrolyte layer close to the negative electrode side, it can be ensured that the polymer is not reduced under low pressure, and by using a low LUMO energy band gap polymer in the first solid electrolyte layer close to the positive electrode side, it can be ensured that it is not oxidized under high pressure, thereby broadening the electrochemical window, alleviating the problem that a single polymer solid electrolyte cannot meet the wide voltage window, and obtaining a polymer system that can adapt to high and low pressures.

[0064] It should be pointed out that the present application does not limit the specific range of the LUMO energy levels of the first polymer solid electrolyte, the second polymer solid electrolyte, the first oxide solid electrolyte, and the second oxide solid electrolyte. As long as the LUMO energy level of the first polymer solid electrolyte is less than the LUMO energy level of the second polymer solid electrolyte, and the LUMO energy level of the first oxide solid electrolyte is less than the LUMO energy level of the second oxide solid electrolyte, a high LUMO energy band gap polymer can be used on the negative electrode side to ensure that the polymer is not reduced under low pressure, and a low LUMO energy band gap can be used on the positive electrode side to ensure that the polymer is not oxidized under high pressure, without limiting the purpose of the present application. The specific LUMO energy level range or value of each substance can be selected according to the specific situation under the above conditions, and will not be listed one by one here.

[0065] It is understood that, when the LUMO energy level of the first oxide solid electrolyte is less than the LUMO energy level of the second oxide solid electrolyte, the specific types of the first oxide solid electrolyte and the second oxide solid electrolyte can be selected from any known electrolyte material. Optionally, the first oxide electrolyte and the second oxide solid electrolyte in the present application can be selected from the solid electrolyte materials listed below.

[0066] In some embodiments, the first oxide solid electrolyte includes, but is not limited to, any one of lithium aluminum titanium phosphate (LATP), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), or lithium aluminum germanium phosphate (LAGP), or a combination of at least two thereof.

[0067] Preferably, the first oxide solid electrolyte is selected from LATP.

[0068] In some embodiments, the second oxide solid electrolyte includes, but is not limited to, lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), Li 2 O.B 2 O 3 , Li 2 O·LiI or Li2 Any one or a combination of at least two of O·LiBr.

[0069] Preferably, the second oxide solid electrolyte is selected from LLZO.

[0070] Thus, the present invention can be used to reduce the glass transition temperature of the polymer and improve the ionic conductivity by using the above-mentioned first oxide solid electrolyte and the second oxide solid electrolyte as the active fillers of the first composite polymer electrolyte and the second composite polymer electrolyte, that is, relying on the nanoparticle size and Lewis alkalinity of the oxide solid electrolyte to reduce the degree of crystallization of the polymer electrolyte, increase the amorphous region, increase the polymer dielectric constant, promote the solubility of lithium salts and the lithium ion transfer coefficient, and at the same time cooperate with the solid electrolyte solid ion transmission and the liquid transmission of the plasticizer to further accelerate the ionic conductivity. In addition, the use of the above-mentioned first oxide solid electrolyte and the second oxide solid electrolyte can meet the condition that the LUMO energy level of the first oxide solid electrolyte is less than the LUMO energy level of the second oxide solid electrolyte.

[0071] It is understood that, when the LUMO energy level of the first polymer solid electrolyte is less than the LUMO energy level of the second polymer solid electrolyte, the specific types of the first polymer solid electrolyte and the second polymer solid electrolyte can be selected from any known electrolyte material. Optionally, the first polymer electrolyte and the second polymer solid electrolyte in the present application can be selected from the solid electrolyte materials listed below.

[0072] In some embodiments, the first polymer solid electrolyte includes a first polymer, a second polymer, and a first lithium salt, and the second polymer solid electrolyte includes a third polymer and a second lithium salt.

[0073] Optionally, in the first polymer solid electrolyte and the second polymer solid electrolyte, the LUMO energy level of the first polymer or the second polymer is smaller than the LUMO energy level of the third polymer.

[0074] In an embodiment of the present application, the first polymer solid electrolyte is mainly composed of a first polymer, a second polymer and a first lithium salt, wherein the first polymer includes, but is not limited to, polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HEP), polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET) or polyimide (PI) Any one or a combination of at least two.

[0075] The second polymer includes, but is not limited to, any one of polyethylene glycol diacrylate (PEGDA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polyimide (PI) or poly(1,3-dioxolane) (PDOL) or a combination of at least two thereof, and the second polymer is of a different type from the first polymer; that is, the first polymer and the second polymer are not simultaneously selected from PVA, PMMA or PI.

[0076] Preferably, the first polymer is selected from PVDF-HEP, and the second polymer is selected from PEGDA.

[0077] The first lithium salt includes, but is not limited to, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium borate oxalate (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium borate difluorooxalate (LiODFB), or lithium nitrate (LiNO 3 ) or a combination of at least two of them.

[0078] Preferably, the first lithium salt is selected from LiTFSI.

[0079] In a preferred embodiment of the present invention, the first polymer is selected from PVDF-HEP, the second polymer is selected from PEGDA, and the first lithium salt is selected from LiTFSI. Thus, the first polymer solid electrolyte is mainly composed of PVDF-HEP, PEGDA and LiTFSI.

[0080] The first polymer solid electrolyte is formed by using PVDF-HEP, PEGDA and LiTFSI. PVDF-HEP and PEGDA are widely available and have better application effects. In addition, the solubility of the used LiTFSI is relatively large, so that the ionic conductivity of the first polymer solid electrolyte is relatively high.

[0081] In an embodiment of the present application, the second polymer solid electrolyte is mainly composed of a third polymer and a second lithium salt, wherein the third polymer includes, but is not limited to, at least one of polymethyl methacrylate (PMMA), polyethylene oxide (PEO), polyacrylonitrile (PAN) or polyvinyl pyrrolidone (PVP), and the third polymer is of a different type from the first polymer and the second polymer; that is, the third polymer, the first polymer and the second polymer are not selected from PMMA, PEO, etc. at the same time.

[0082] Preferably, the third polymer is selected from PMMA.

[0083] The second lithium salt includes, but is not limited to, LiTFSI, LiPF 6 , LiBF4 , LiBOB, LiFSI, LiODFB or LiNO 3 Any one or a combination of at least two of the following.

[0084] Preferably, the second lithium salt is selected from LiTFSI.

[0085] In the present application, the first lithium salt and the second lithium salt may be of the same type, or may be of different types, and this is not limited.

[0086] In a preferred embodiment of the present invention, the third polymer is selected from PMMA, and the second lithium salt is selected from LiTFSI. Thus, the second polymer solid electrolyte is mainly composed of PMMA and LiTFSI.

[0087] The second polymer solid electrolyte formed by using PMMA and LiTFSI has a wide source of PMMA and a better application effect, and the used LiTFSI has a large solubility. The second polymer solid electrolyte formed by PMMA and LiTFSI has a high ion migration number.

[0088] In some embodiments, in the first composite polymer electrolyte, the mass ratio of the first polymer, the second polymer, the first lithium salt, and the first oxide solid electrolyte is (20-30): (5-10): (20-30): (30-40). As an example, the mass ratio of the first polymer, the second polymer, the first lithium salt, and the first oxide solid electrolyte can be 30:10:30:30, 30:5:25:40, 30:8:24:38, 20:10:30:40, etc.

[0089] By controlling the mass ratio of the first polymer, the second polymer, the first lithium salt and the first oxide solid electrolyte within the above range, the synergistic effect of each substance can be fully exerted, and the first oxide solid electrolyte can effectively play the role of lowering the glass transition temperature of the polymer and improving the ionic conductivity as an active filler, thereby avoiding the problem of affecting other properties of the composite electrolyte or weakening the above-mentioned effects due to excessive or insufficient content of the first oxide solid electrolyte, or avoiding the problem of difficulty in film formation or too low conductivity of the composite solid electrolyte or even difficulty in ion conduction due to excessive or insufficient content of the first lithium salt.

[0090] In some embodiments, in the second composite polymer electrolyte, the mass ratio of the third polymer, the second lithium salt, and the second oxide solid electrolyte is (20-35): (10-20): (40-60). As an example, the mass ratio of the third polymer, the second lithium salt, and the second oxide solid electrolyte can be 20:20:60, 25:15:60, 25:20:55, 30:10:60, 30:20:50, 35:10:55, 30:20:50, etc.

[0091] By controlling the mass ratio of the third polymer, the second lithium salt and the second oxide solid electrolyte within the above range, the synergistic effect of each substance can be fully exerted, and the second oxide solid electrolyte can effectively play the role of lowering the glass transition temperature of the polymer and improving the ionic conductivity as an active filler, thereby avoiding the problem of affecting other properties of the composite electrolyte or weakening the above-mentioned effects due to excessive or insufficient content of the second oxide solid electrolyte, or avoiding the problem of difficulty in film formation or too low conductivity of the composite solid electrolyte or even difficulty in ion conduction due to excessive or insufficient content of the second lithium salt.

[0092] In some embodiments, the particle size of the first oxide solid electrolyte in the first composite polymer electrolyte presents a gradient distribution, and the particle size of the first oxide solid electrolyte presents a decreasing trend along the direction approaching the positive electrode.

[0093] In some embodiments, the concentration of the first oxide solid electrolyte in the first composite polymer electrolyte presents a gradient distribution, and the concentration of the first oxide solid electrolyte presents a decreasing trend along the direction close to the positive electrode.

[0094] In the present application, in the first composite polymer electrolyte, the particle size and / or concentration of the first oxide solid electrolyte may be distributed in a gradient, such as the particle size of the first oxide solid electrolyte is distributed in a gradient, or the concentration of the first oxide solid electrolyte is distributed in a gradient, or both the particle size and concentration of the first oxide solid electrolyte are distributed in a gradient. Moreover, along the direction close to the positive electrode, the particle size and / or concentration of the first oxide solid electrolyte in the first solid electrolyte layer presents a decreasing trend, that is, the particle size and / or concentration of the first oxide solid electrolyte gradually increases from the surface of the first solid electrolyte layer in contact with the positive electrode to the surface in contact with the second solid electrolyte layer.

[0095] In some embodiments, the particle size of the second oxide solid electrolyte in the second composite polymer electrolyte presents a gradient distribution, and the particle size of the second oxide solid electrolyte presents an increasing trend along the direction approaching the negative electrode.

[0096] In some embodiments, the concentration of the second oxide solid electrolyte in the second composite polymer electrolyte presents a gradient distribution, and the concentration of the second oxide solid electrolyte presents an increasing trend along the direction approaching the negative electrode.

[0097] In the present application, in the second composite polymer electrolyte, the particle size and / or concentration of the second oxide solid electrolyte may be distributed in a gradient, such as the particle size of the second oxide solid electrolyte is distributed in a gradient, or the concentration of the second oxide solid electrolyte is distributed in a gradient, or both the particle size and concentration of the second oxide solid electrolyte are distributed in a gradient. Moreover, along the direction close to the negative electrode, the particle size and / or concentration of the second oxide solid electrolyte in the second fixed electrolyte layer presents an increasing trend, that is, the particle size and / or concentration of the second oxide solid electrolyte gradually increases from the surface of the second solid electrolyte layer in contact with the first solid electrolyte layer to the surface in contact with the negative electrode.

[0098] In the preparation process of the first composite polymer electrolyte and the second composite polymer electrolyte of the present application, the polymer is melted at high temperature and an oxide solid electrolyte active filler is added. The different sedimentation rates of particles of different particle sizes under the action of gravity are utilized, and at the same time, the solidification rate of the polymer is coordinated to form a spatial distribution state in which small particles are on the top and large particles are on the bottom. This structure can reduce the glass transition temperature and dielectric constant of the polymer close to the electrode side, form a local high-concentration dissociated lithium salt structure, and promote ion transport. The large particles at the bottom of the first composite polymer electrolyte and the second composite polymer electrolyte cooperate with the polymer on the upper layer to ensure high mechanical strength and meet high ionic conductivity and strong mechanical strength.

[0099] Optionally, the particle sizes of the first oxide solid electrolyte and the second oxide solid electrolyte can both be nanometer-scale, such as both can be in the range of 10nm to 500nm. And the first oxide solid electrolyte and the second oxide solid electrolyte can respectively include particle sizes of different levels in the range of 10nm to 500nm. For example, the first oxide solid electrolyte and the second oxide solid electrolyte can respectively include a system consisting of a plurality of different particle size levels such as 10nm to 50nm, 100nm to 200nm, 400nm to 500nm, or can also respectively include a system consisting of a plurality of different particle size levels such as 10nm to 30nm, 80nm to 100nm, 200nm to 250nm, 450nm to 500nm, etc., and this application does not limit this.

[0100] As an example, in the vertical direction, in the solid-state battery, the positive electrode, the first solid electrolyte layer, the second solid electrolyte layer and the negative electrode are stacked in sequence from top to bottom. The particle size and / or concentration of the first oxide solid electrolyte in the first composite polymer electrolyte in the first solid electrolyte layer increases from top to bottom, and the particle size and / or concentration of the second oxide solid electrolyte in the second composite polymer electrolyte in the second solid electrolyte layer increases from top to bottom.

[0101] Thus, the mechanical strength and ionic conductivity can be controlled by gradient-adjusting the crystallinity of the polymer. Specifically, the polymer is melted at a high temperature and an oxide solid electrolyte active filler is added. The different sedimentation rates of particles of different sizes under the action of gravity are utilized. At the same time, the solidification rate of the polymer is coordinated to form a spatial distribution state in which small particles are on the top and large particles are on the bottom. This structure can reduce the glass transition temperature and dielectric constant of the polymer close to the electrode side, form a local high-concentration dissociated lithium salt structure, and promote ion transport. The large particles at the bottom of the first composite polymer electrolyte and the second composite polymer electrolyte cooperate with the polymer on the upper layer to ensure high-strength mechanical strength and meet high ionic conductivity and strong mechanical strength.

[0102] Moreover, a synergistic effect of ion migration between the upper and lower chain segments can be formed, specifically: a first oxide solid electrolyte (such as LATP) is added to the first solid electrolyte layer near the positive electrode side, and the first oxide solid electrolyte presents a gradient distribution in the vertical direction between the layers of the first polymer and the second polymer (such as PVDF-HFP and PEGDA) mixture, such as the particle size and concentration of the first oxide solid electrolyte present a gradient distribution, thereby the glass transition temperature in the vertical direction between the layers also presents a gradient change, and the mass fraction of the amorphous region near the positive electrode side is the smallest. Similarly, the same is true for adding a second oxide solid electrolyte (such as LLZO) to the second solid electrolyte layer near the negative electrode side, and the second oxide solid electrolyte presents a gradient distribution in the vertical direction between the layers of the third polymer, such as the particle size and concentration (particle density) of the second oxide solid electrolyte present a gradient distribution, and the amorphous mass fraction of the second oxide solid electrolyte near the negative electrode in the second solid electrolyte layer near the negative electrode side accounts for the largest proportion. Thus, the lithium ion amorphous region undergoes segment migration to transfer lithium ions. In the vertical direction of the polymer solid electrolyte, the lithium ion transfer segments in the amorphous region between the segments present a gradient increasing trend, which can accelerate the lithium ion transfer speed.

[0103] In some embodiments, the first solid electrolyte layer further includes a first plasticizer, and the second solid electrolyte layer further includes a second plasticizer. That is, the first solid electrolyte layer is mainly composed of the first composite polymer electrolyte and the first plasticizer, and the second solid electrolyte layer is mainly composed of the second composite polymer electrolyte and the second plasticizer.

[0104] In the present application, by adding the above-mentioned first plasticizer and second plasticizer (collectively referred to as plasticizers), the crystal state of the polymer solid electrolyte can be adjusted, the dissociation of lithium salt can be promoted, and the cation migration number can be increased.

[0105] At the same time, the above-mentioned plasticizers and oxide solid electrolytes can cooperate to strengthen the interface contact between the composite solid electrolyte membrane and the positive or negative electrode. That is, while using the method of adding polymers and active fillers to lower the glass transition temperature, increase the amorphous area, and increase the flexibility of the polymer, adding plasticizers can increase the flexibility of the material while ensuring mechanical strength, thereby enhancing the contact with the positive and negative electrodes and reducing the interface resistance.

[0106] In some embodiments, the first plasticizer includes, but is not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or propylene carbonate (PC).

[0107] In some embodiments, the second plasticizer includes, but is not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or propylene carbonate (PC).

[0108] In the present application, the first plasticizer and the second plasticizer may be of the same type, or may be of different types, and this is not limited.

[0109] In some embodiments, the mass fraction of the first plasticizer in the first solid electrolyte layer is 1% to 2%. As an example, the mass fraction of the first plasticizer in the first solid electrolyte layer can be 1%, 1.2%, 1.5%, 1.8%, 2%, etc.

[0110] In some embodiments, the mass fraction of the second plasticizer in the second solid electrolyte layer is 1% to 2%. As an example, the mass fraction of the second plasticizer in the second solid electrolyte layer can be 1%, 1.2%, 1.5%, 1.8%, 2%, etc.

[0111] In some embodiments, the thickness of the first solid electrolyte layer is A, the thickness of the second solid electrolyte layer is B, and A and B satisfy: 4 / 10≤A / (A+B)≤6 / 10.

[0112] In some embodiments, 5 μm≤A+B≤30 μm.

[0113] In the present application, the energy density and ion conductivity of the battery can be ensured by making the thickness A of the first solid electrolyte layer and the thickness B of the second solid electrolyte layer satisfy the above relationship. This is because the thickness of each of the first solid electrolyte layer and the second solid electrolyte layer cannot be too thin, otherwise the anti-oxidation and anti-reduction capabilities of the corresponding layer cannot be maintained, and the thickness of each of the first solid electrolyte layer and the second solid electrolyte layer cannot be too thick, otherwise the solid electrolyte layer will reduce the energy density of the battery and reduce the ion conductivity.

[0114] In a second aspect, in some embodiments, the present application provides a method for preparing a solid-state battery, which comprises the following steps:

[0115] S1, mixing a raw material for preparing a first polymer solid electrolyte and a first active filler to obtain a first mixed solution, and subjecting the first mixed solution to a cross-linking polymerization reaction to obtain a first solid electrolyte layer, wherein the first active filler includes a first oxide solid electrolyte;

[0116] S2, mixing a raw material for preparing a second polymer solid electrolyte and a second active filler to obtain a second mixed solution, and subjecting the second mixed solution to an in-situ polymerization reaction to obtain a second solid electrolyte layer, wherein the second active filler includes a second oxide solid electrolyte;

[0117] S3, compounding the first solid electrolyte layer and the second solid electrolyte layer to obtain a composite solid electrolyte membrane;

[0118] S4. Place the composite solid electrolyte membrane between the positive electrode and the negative electrode, with the first solid electrolyte layer close to the positive electrode and the second solid electrolyte layer close to the negative electrode, to obtain a solid-state battery.

[0119] It should be understood that the “method for preparing a solid-state battery” and the aforementioned “solid-state battery” are based on the same inventive concept, and all the features and advantages described above for the “solid-state battery” are also applicable to the “method for preparing a solid-state battery” and will not be elaborated here one by one.

[0120] In the present application, the first solid electrolyte layer and the second solid electrolyte layer can be prepared separately, and then the first solid electrolyte layer and the second solid electrolyte layer are combined to form a composite solid electrolyte membrane, and then the positive electrode, the prepared composite solid electrolyte membrane and the negative electrode are assembled together to obtain a solid-state battery. The preparation method of the solid-state battery is simple in process, easy to operate, and has strong feasibility. It is easy to implement in process, and the prepared composite solid electrolyte membrane has excellent performance and low cost, and is easy to realize industrial production.

[0121] In some specific embodiments, the method for preparing the solid-state battery includes the following steps S1 to S4:

[0122] Step S1, preparing a first solid electrolyte layer.

[0123] In some embodiments, in step S1, the raw materials for preparing the first polymer solid electrolyte and the first active filler are mixed to obtain a first mixed solution, specifically comprising: firstly mixing the first polymer and the first solvent evenly, then adding the second polymer, the photoinitiator and the first lithium salt, mixing evenly to obtain a first intermediate mixed solution, mixing the first intermediate mixed solution with the first active filler to obtain a first mixed solution; and then subjecting the first mixed solution to a cross-linking polymerization reaction to obtain a first solid electrolyte layer.

[0124] Optionally, in step S1, the first solvent includes, but is not limited to, at least one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP) or polyethylene glycol (PEG). Optionally, the first polymer includes, but is not limited to, at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyvinylidene fluoride, polyvinyl alcohol, polymethyl methacrylate, polyethylene terephthalate or polyimide. The second polymer includes, but is not limited to, at least one of polyethylene glycol diacrylate, polyvinyl alcohol, polymethyl methacrylate, polyimide or poly (1,3-dioxolane), and the second polymer is of a different type from the first polymer. The first lithium salt includes, but is not limited to, LiTFSI, LiPF 6 , LiBF 4 , LiBOB, LiFSI, LiODFB or LiNO 3 At least one of .

[0125] Optionally, in step S1, the cross-linking polymerization reaction is carried out under the action of a photoinitiator and under the irradiation of ultraviolet light.

[0126] In the present application, the photoinitiator may be a common photoinitiator of a UV curing system, and the amount of the photoinitiator may be added in small amounts according to actual conditions, without limitation. As an example, the photoinitiator may be selected from 3,6,9-photoinitiator.

[0127] In some embodiments, the intensity of the UV light is 220 mW / cm 2 Up to 230mW / cm 2 As an example, the intensity of ultraviolet light is 220 mW / cm 2 、222mW / cm 2 、225mW / cm 2 、227mW / cm 2 、230mW / cm 2 wait.

[0128] Exemplarily, the above step S1 specifically includes: adding a certain amount of a first polymer (such as PVDF-HFP, etc.) to a first solvent (such as DMF, etc.) in a glove box, and completely dissolving it at a high temperature (temperature range of 55°C to 85°C); then adding a second polymer (such as PEGDA, etc.), a very small amount of photoinitiator such as 3,6,9-photoinitiator and a first lithium salt (such as LITFSI, etc.), continuing to stir at the above temperature until completely dissolved, transferring the completely dissolved uniform solution to a circular culture dish at room temperature, adding a first oxide solid electrolyte (such as LATP, etc.), using a UV lamp with an ultraviolet intensity of 227mW for a certain time to cross-link and polymerize PEGDA to form a network (such as PEGDA self-crosslinking and cross-linking with PVDF-HFP to form a network), and then placing the culture dish at a certain temperature (temperature range of 80°C to 120°C) and heating for about 8 hours, and finally obtaining a first solid electrolyte layer (such as obtaining a PVDF-HFP / PEGDA / LITFSI@LATP polymer composite solid electrolyte film).

[0129] In addition, during the preparation of the first solid electrolyte, a first thickener may be added, and the order of adding the first thickener may be selectively set by a person skilled in the art according to actual needs, and is not limited thereto. For example, the first thickener may be added in step S1, or, in a subsequent step S4, after a battery cell comprising a positive electrode, a negative electrode and a composite solid electrolyte membrane is prepared, a certain amount of the first thickener may be injected into the battery cell.

[0130] Step S2: preparing a second solid electrolyte layer.

[0131] In some embodiments, in step S2, the raw material for preparing the second polymer solid electrolyte and the second active filler are mixed to obtain a second mixed solution, specifically comprising: mixing the second active filler with a dispersant and a second solvent, and then adding a second lithium salt and a monomer for forming a third polymer to obtain a second mixed solution. The second mixed solution is then subjected to an in-situ polymerization reaction to obtain a second solid electrolyte layer.

[0132] Optionally, in step S2, the second solvent includes, but is not limited to, at least one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP) or polyethylene glycol (PEG).

[0133] In the present application, the first solvent and the second solvent may be of the same type, or may be of different types, and there is no limitation on this.

[0134] Optionally, the dispersant includes alcohols. For example, the dispersant is an alcohol dispersant such as methanol, ethanol, propanol, etc. Optionally, the third polymer includes, but is not limited to, at least one of polymethyl methacrylate, polyethylene oxide, polyacrylonitrile, or polyvinyl pyrrolidone, and the third polymer is of a different type from the first polymer and the second polymer. The second lithium salt includes, but is not limited to, LiTFSI, LiPF 6 , LiBF 4 , LiBOB, LiFSI, LiODFB or LiNO 3 At least one of .

[0135] Optionally, in step S2, the second mixed solution further contains an initiator, and the initiator includes, but is not limited to, azobisisobutyronitrile (AIBN).

[0136] In some embodiments, the conditions of the in-situ polymerization reaction include: a temperature of 70°C to 100°C, a time of 20min to 60min, and a rotation speed of 300r / min to 1000r / min. As an example, the temperature may be 70°C, 80°C, 90°C, 100°C, etc.; the time may be 20min, 30min, 40min, 50min, 60min, etc.; the rotation speed may be 300rpm, 400rpm, 500rpm, 400rpm, 500rpm, 600rpm, 800rpm, 900rpm, 1000rpm, etc.

[0137] Exemplarily, the above step S2 specifically includes: dispersing a second oxide solid electrolyte (such as LLZO, etc.) in a dispersant (such as methanol, etc.), adding a certain amount of a second solvent (such as DMF, etc.) into a 50mL centrifuge tube, mixing the methanol dispersion containing LLZO therewith, and then adding a second lithium salt (such as LITFSI, etc.), a monomer for forming a third polymer (such as MMA monomer, etc.) and an initiator such as AIBN initiator to the mixed solution for ultrasonic dissolution, followed by heating in a water bath at a certain temperature (temperature range of 70°C to 100°C), and conducting an in-situ polymerization reaction at 300r / min to 1000r / min (such as about 500r / min) under magnetic stirring for 20min to 60min. After the reaction is completed, the mixed solution is naturally cooled to room temperature, and then the pretreated glass substrate is fixed on a spin coater, and the mixed solution is dripped on the surface of the substrate at a rotation speed of 2000r / min for 10s. Then, the spin-coated film is placed in an oven and dried overnight at 50° C. to 80° C. to evaporate the residual solvent, thereby obtaining a second solid electrolyte layer (such as a PMMA / LITFSI@LLZO composite polymer solid electrolyte film).

[0138] In addition, during the preparation of the second solid electrolyte, a second thickener may be added, and the order of adding the second thickener may be selectively set by a person skilled in the art according to actual needs, and is not limited thereto. For example, the second thickener may be added in step S2, or, in a subsequent step S4, after a battery cell comprising a positive electrode, a negative electrode and a composite solid electrolyte membrane is prepared, a certain amount of the second thickener may be injected into the battery cell.

[0139] Step S3, compounding the first solid electrolyte layer and the second solid electrolyte layer.

[0140] In some embodiments, in step S3, the first solid electrolyte layer and the second solid electrolyte layer are placed alternately up and down, and pressurized at 5 MPa for 10 minutes at a temperature of 60°C to 120°C to obtain a composite solid electrolyte membrane, that is, a double-layer polymer solid electrolyte membrane.

[0141] Step S4: preparing a solid-state battery.

[0142] In step S4, a positive electrode and a negative electrode are first provided. Optionally, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector. Optionally, the negative electrode includes a positive electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector; or, the negative electrode can be selected from a lithium metal negative electrode.

[0143] It should be noted here that in the embodiments of the present application, there is no limitation on the specific materials, structures, etc. of the positive electrode current collector, the positive electrode active material layer or the negative electrode in the positive electrode, and the positive electrode and negative electrode structures and components that are well known in the art and can be used for secondary batteries can be selected.

[0144] Then, the composite solid electrolyte membrane obtained in step S3 is placed between the positive electrode and the negative electrode, with the first solid electrolyte layer close to the positive electrode and the second solid electrolyte layer close to the negative electrode, to obtain a solid-state battery.

[0145] Optionally, after the positive electrode, the composite solid electrolyte membrane and the negative electrode are composited, a battery cell is obtained, and the stacked battery cell is hot-pressed and placed in an aluminum-plastic film for top and side sealing. Then liquid injection is performed, such as injecting a plasticizer into the battery, and the liquid injection coefficient can be about 0.1g / Ah; then packaging is performed, that is, the battery after liquid injection is sealed. After chemical formation and other processes, a solid-state battery can be obtained.

[0146] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.

[0147] Example 1

[0148] 1. Preparation of a composite solid electrolyte membrane, comprising the following steps:

[0149] (1) Preparation of the first solid electrolyte layer:

[0150] 0.4 g of the first polymer PVDF-HFP is added to the first solvent DMF, and stirred at 65°C until completely dissolved; then 0.04 g of the second polymer PEGDA, a very small amount (such as about 0.001 g) of 3,6,9-photoinitiator and 0.44 g of the first lithium salt LITFSI are added, and stirring is continued at the same temperature until completely dissolved, and the completely dissolved uniform solution is transferred to a circular culture dish at room temperature, and 0.6 g of the first oxide solid electrolyte LATP is added, and a UV lamp is used to irradiate with an ultraviolet intensity of 227 mW for 20 minutes to cross-link and polymerize PEGDA to form a network (such as PEGDA self-crosslinking and cross-linking with PVDF-HFP to form a network), and then the culture dish is placed on a heating table at 90°C and heated for 8 hours to obtain a 4 μm first solid electrolyte layer (such as obtaining a PVDF-HFP / PEGDA / LITFSI@LATP polymer composite solid electrolyte film).

[0151] (2) Preparation of the second solid electrolyte layer:

[0152] 1g of the second oxide solid electrolyte LLZO is dispersed in methanol, a certain amount (about 5mL) of the second solvent DMF is added to a 50mL centrifuge tube, and the methanol dispersion containing LLZO is mixed with it, and then 0.5g of the second lithium salt LITFSI, a monomer for forming a third polymer such as MMA monomer 1.5g and AIBN initiator 30mg are added to the mixed solution for ultrasonic dissolution, followed by heating in a water bath at 85°C, and in-situ polymerization reaction is carried out under magnetic stirring at 500r / min for 30min. After the reaction is completed, the mixed solution is naturally cooled to room temperature, and then the pretreated glass substrate is fixed on a spin coater, and the mixed solution is dripped on the surface of the substrate at a speed of 2000r / min for 10s. Then, the spin-coated film is placed in an oven and dried overnight at 65°C to evaporate the residual solvent to obtain a 5μm second solid electrolyte layer (such as a PMMA / LITFSI@LLZO composite polymer solid electrolyte film).

[0153] (3) The first solid electrolyte layer and the second solid electrolyte layer are placed alternately up and down, and pressurized at 80° C. and 5 MPa for 10 min to obtain a composite solid electrolyte membrane.

[0154] 2. Preparation of solid-state batteries, including:

[0155] (1) Preparation of positive electrode:

[0156] The binder styrene butadiene rubber (SBR) is dissolved in a non-polar solvent (xylene) and fully dissolved to obtain a mixed solution; the positive electrode active material ternary material NCM, solid electrolyte (sulfide electrolyte LPSC), and conductive agent vapor-grown carbon fiber (VGCF) are dry-mixed and fully ground for more than 1 hour to obtain a uniformly mixed mixed material; the above mixed material is added to the above mixed solution to obtain a positive electrode slurry (the mass ratio of positive electrode active material, solid electrolyte, binder and conductive agent is 79:19:1:1), and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode is made through drying, sheeting and other processes. The size of the positive electrode is 96mm×51mm.

[0157] (2) Preparation of negative electrode:

[0158] A negative electrode is obtained by using lithium foil as the negative electrode active material and bonding it to the negative electrode current collector copper foil.

[0159] The size of the negative electrode is 100 mm × 55 mm.

[0160] (3) Battery assembly:

[0161] The assembly is carried out by soft-pack lamination, including: laminating the positive electrode, composite solid electrolyte membrane, and negative electrode in order to obtain a battery cell; hot-pressing the stacked battery cell and placing it in an aluminum-plastic film for top and side sealing; then injecting liquid to inject the plasticizer (DMC) into the battery cell with an injection coefficient of 0.1g / Ah; and then encapsulating and sealing the battery after injection. Then, the packaged battery is subjected to formation treatment to obtain a solid-state battery. It is worth noting that when comparing the electrochemical properties of different positive electrode sheets, the load capacity of the negative electrode remains basically the same.

[0162] Example 2

[0163] The difference between Example 2 and Example 1 is that:

[0164] In the first solid electrolyte layer, 0.03 g of the second polymer PEGDA, 0.33 g of the first lithium salt LITFSI, and 0.8 g of the first oxide solid electrolyte LATP were added.

[0165] The rest are the same as in Example 1.

[0166] Example 3

[0167] The difference between Example 3 and Example 1 is that:

[0168] In the first solid electrolyte layer, 0.05 g of the second polymer PEGDA, 0.55 g of the first lithium salt LITFSI, and 0.4 g of the first oxide solid electrolyte LATP were added.

[0169] The rest are the same as in Example 1.

[0170] Example 4

[0171] The difference between Example 4 and Example 1 is that:

[0172] In the second solid electrolyte layer, 0.5 g of the second oxide solid electrolyte LLZO, 0.02 g of the AIBN initiator, and 0.4 g of the second lithium salt LITFSI were added.

[0173] The rest are the same as in Example 1.

[0174] Example 5

[0175] The difference between Example 5 and Example 1 is that:

[0176] In the second solid electrolyte layer, 1.5 g of the second oxide solid electrolyte LLZO, 0.04 g of the AIBN initiator, and 0.6 g of the second lithium salt LITFSI were added.

[0177] The rest are the same as in Example 1.

[0178] Example 6

[0179] The difference between Example 6 and Example 1 is that:

[0180] In the first solid electrolyte layer, the first polymer is PEO, the second polymer is PDOL, and the first lithium salt is LiPF 6 , the first oxide solid electrolyte uses LLZTO.

[0181] In the second solid electrolyte layer, the monomer used to form the third polymer is MMA, the second lithium salt is LiODFB, and the second oxide solid electrolyte is LATP.

[0182] The rest are the same as in Example 1.

[0183] Example 7

[0184] The difference between Example 7 and Example 1 is that:

[0185] In the first solid electrolyte layer, the first polymer is PMMA, the second polymer is PDOL, the first lithium salt is LiODFB, and the first oxide solid electrolyte is LATP.

[0186] In the second solid electrolyte layer, the monomer used to form the third polymer is EO, and the second lithium salt is LiNO 3 , the second oxide solid electrolyte adopts LLTO.

[0187] The rest are the same as in Example 1.

[0188] Example 8

[0189] The difference between Example 8 and Example 1 is that:

[0190] The thickness of the first solid electrolyte layer is 3 μm; the thickness of the second solid electrolyte layer is 5 μm.

[0191] The rest are the same as in Example 1.

[0192] Comparative Example 1

[0193] The main difference between Comparative Example 1 and Example 1 is:

[0194] The composite solid electrolyte membrane of Comparative Example 1 omits the second solid electrolyte layer, that is, the solid electrolyte membrane of Comparative Example 1 only contains the first solid electrolyte layer.

[0195] The rest are the same as in Example 1.

[0196] Comparative Example 2

[0197] The main difference between Comparative Example 2 and Example 1 is:

[0198] The composite solid electrolyte membrane of Comparative Example 2 omits the first solid electrolyte layer, that is, the solid electrolyte membrane of Comparative Example 1 only contains the second solid electrolyte layer.

[0199] The rest are the same as in Example 1.

[0200] Comparative Example 3

[0201] The main difference between Comparative Example 3 and Example 1 is:

[0202] In the first solid electrolyte layer of the composite solid electrolyte membrane of Comparative Example 3, the first oxide solid electrolyte LATP is omitted.

[0203] The rest are the same as in Example 1.

[0204] Comparative Example 4

[0205] The main difference between Comparative Example 4 and Example 1 is:

[0206] In the second solid electrolyte layer of the composite solid electrolyte membrane of Comparative Example 4, the second oxide solid electrolyte LLZO is omitted.

[0207] The rest are the same as in Example 1.

[0208] Comparative Example 5

[0209] The main difference between Comparative Example 5 and Example 1 is:

[0210] In the composite solid electrolyte membrane of Comparative Example 5, the first oxide solid electrolyte LATP is omitted in the first solid electrolyte layer, and the second oxide solid electrolyte LLZO is omitted in the second solid electrolyte layer.

[0211] The rest are the same as in Example 1.

[0212] Comparative Example 6

[0213] The main difference between Comparative Example 6 and Example 1 is:

[0214] In the composite solid electrolyte membrane of Comparative Example 6, only the first oxide solid electrolyte LATP is added to the first solid electrolyte layer, and only the second oxide solid electrolyte LLZO is added to the second solid electrolyte layer (only oxide solid electrolyte is added to the composite solid electrolyte membrane).

[0215] The rest are the same as in Example 1.

[0216] Performance Testing

[0217] The composite solid electrolyte membranes and solid-state batteries obtained in the above-mentioned embodiments and comparative examples were subjected to performance tests.

[0218] 1. First coulomb efficiency (first effect) test: After the solid-state batteries in each embodiment and comparative example are manufactured, they are first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.25V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.25V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.8V at a constant current of 1C to obtain the discharge capacity C2, and then discharged to 2.8V at a constant current of 0.1C to obtain the discharge capacity C3, and then discharged to 2.8V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first effect) is calculated according to (C2+C3+C4) / (C0+C1)*100%.

[0219] 2. Cycle performance (2000 cycle capacity retention rate) test: Take the solid-state batteries in the above embodiments and comparative examples after the capacity division is completed, first charge them to 4.25V with a constant current of 1C, and then charge them to I≤0.05C with a constant voltage of 4.25V; after standing for 5 minutes, discharge the battery to 2.8V with a constant current of 1C to obtain the discharge capacity C1; stand for 30 minutes. Repeat the above steps 1999 times to obtain the discharge capacity C2000; the 2000 cycle capacity retention rate is calculated according to (C2000) / (C1)*100%.

[0220] 3. Ionic conductivity test: Use electrochemical testing equipment (such as Solid X equipment, which integrates film making, testing, data acquisition and analysis functions) to measure the resistance RL using the AC impedance method. For example, use a button battery test clip to clamp the two sides of the treated electrolyte sheet, set the test parameters, start the EIS test, obtain the AC impedance curve through the EIS test, and calculate the ionic conductivity. Usually, the AC impedance curve of the electrolyte sheet is divided into two sections. The first section is the semicircle of the grain boundary capacitance arc, and the second section is the straight line with an upward tilt of the electrode response diffusion tail. The value of the inflection point of the semicircle and the straight line on the real axis z' is taken as the total impedance to calculate the ionic conductivity.

[0221] For example, the thickness d of the electrolyte membrane is measured using a micrometer, and S is used to represent the area of ​​the membrane. The area S of the membrane is always 1 cm 2 (The membrane is a 1×1 cm stainless steel sheet); then, the ionic conductivity к can be calculated by the following formula: к=d / (RL·S).

[0222] 4. Composite solid electrolyte membrane area shrinkage test (under 250℃): Cut 3 square diaphragms of 100mm×100mm in the longitudinal direction of the membrane roll; Note that when cutting the diaphragm, one edge should be parallel to the longitudinal edge of the diaphragm, the maximum deviation angle should not exceed 5°, and the longitudinal and transverse markings should be done; If the diaphragm width is less than 100mm, the sampling size should be 100mm×diaphragm width. Place the stainless steel plate and two quantitative filter papers in the middle of the oven, control the temperature so that the stainless steel plate and filter paper reach (90±1)℃ or (250±1)℃; Mark the longitudinal and transverse directions of the diaphragm, and use the length measuring instrument with corresponding resolution to measure the longitudinal and transverse lengths of the sample respectively; Place the diaphragm flat on one of the quantitative filter papers on the stainless steel plate in the middle of the blast thermostat, press it with another quantitative filter paper, and close the thermostat door; Keep it at 90℃ for 2h±12min, or at 250℃ for 1h±6min. After heating, take out the diaphragm, wait for the diaphragm to return to room temperature, and measure the longitudinal and transverse marking lengths again. Calculate the longitudinal and transverse shrinkage of the diaphragm according to the formula (diaphragm shrinkage = L (250 ° C) / L (90 ° C) * 100%), and take the average of the three test results as the thermal shrinkage of the diaphragm.

[0223] The test results are shown in Table 1 below.

[0224] Table 1

[0225]

[0226] As can be seen from Table 1, compared with Comparative Examples 1 to 6, the solid-state battery prepared by using the composite solid electrolyte membrane provided by Examples 1 to 8 of the present invention plays a positive role in improving the first coulomb efficiency and cycle performance of the battery; this is mainly due to the improvement of the ionic conductivity of the composite solid electrolyte membrane provided by the embodiment of the present invention. In addition, compared with Comparative Examples 1 to 5, the area shrinkage rate of the composite solid electrolyte membrane provided by Examples 1 to 8 of the present invention at high temperature is relatively low, indicating that the composite solid electrolyte membrane of the present invention has strong thermal stability.

[0227] also, Figure 1 The SEM diagram of the composite solid electrolyte membrane prepared in Example 1 of the present invention is shown, wherein PVDF-HFP / PEGDA / LITFSI@LATP represents the first solid electrolyte layer, and PMMA / LITFSI@LLZO represents the second solid electrolyte layer. Figure 1 From the SEM image, we can see that the composite solid electrolyte membrane is a double-layer hybrid structure. The second solid electrolyte layer near the negative electrode side uses a high LUMO band gap polymer to ensure that the polymer is not reduced under low pressure. The first solid electrolyte layer near the positive electrode side uses a low LUMO band gap to ensure that it is not oxidized under high pressure. This structure can combine the characteristics of the polymer to inhibit dendrite growth. At the same time, it relies on active fillers to reduce the glass transition temperature, increase the amorphous area, and increase the flexibility of the polymer. At the same time, it uses the addition of plasticizers to increase the flexibility of the material while ensuring mechanical strength, so as to enhance the contact with the positive and negative electrodes and reduce the interface resistance. This application reduces the glass transition temperature of the polymer by adding active fillers to improve the ionic conductivity. The oxide solid electrolyte is used as an active filler, and the nanoparticle size and Lewis alkalinity of the solid electrolyte are used to reduce the crystallinity of the polymer electrolyte, increase the amorphous area, increase the polymer dielectric constant, promote the solubility of lithium salts and the lithium ion transfer coefficient, and cooperate with the solid electrolyte solid ion transmission and the liquid transmission of the plasticizer to further accelerate the ionic conductivity.

[0228] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0229] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0230] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0231] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0232] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode, a negative electrode and a composite solid electrolyte membrane located between the positive electrode and the negative electrode; The composite solid electrolyte membrane includes a first solid electrolyte layer and a second solid electrolyte layer disposed on the surface of the first solid electrolyte layer, the first solid electrolyte layer is close to the positive electrode, and the second solid electrolyte layer is close to the negative electrode; The first solid electrolyte layer includes a first composite polymer electrolyte, the first composite polymer electrolyte includes a first polymer solid electrolyte and a first active filler, and the first active filler includes a first oxide solid electrolyte; The second solid electrolyte layer includes a second composite polymer electrolyte, the second composite polymer electrolyte includes a second polymer solid electrolyte and a second active filler, and the second active filler includes a second oxide solid electrolyte.

2. The solid-state battery according to claim 1, characterized in that: The LUMO energy level of the first polymer solid electrolyte is lower than the LUMO energy level of the second polymer solid electrolyte; and / or, A LUMO energy level of the first oxide solid electrolyte is lower than a LUMO energy level of the second oxide solid electrolyte.

3. The solid-state battery according to claim 1, characterized in that: The first oxide solid electrolyte comprises at least one of LATP, LLZTO or LAGP; and / or, The second oxide solid electrolyte includes at least one of LLZO, LLTO, Li2O·B2O3, Li2O·LiI or Li2O·LiBr.

4. The solid-state battery according to claim 1, characterized in that: The first polymer solid electrolyte includes a first polymer, a second polymer and a first lithium salt, and the second polymer solid electrolyte includes a third polymer and a second lithium salt; The first composite polymer electrolyte and the second composite polymer electrolyte satisfy at least one of the following characteristics (1) to (7): (1) the first polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyvinylidene fluoride, polyvinyl alcohol, polymethyl methacrylate, polyethylene terephthalate or polyimide; (2) the second polymer comprises at least one of polyethylene glycol diacrylate, polyvinyl alcohol, polymethyl methacrylate, polyimide or poly(1,3-dioxolane), and the second polymer is of a different type from the first polymer; (3) the third polymer comprises at least one of polymethyl methacrylate, polyethylene oxide, polyacrylonitrile or polyvinyl pyrrolidone, and the third polymer is of a different type from the first polymer and the second polymer; (4) The first lithium salt includes at least one of LiTFSI, LiPF6, LiBF4, LiBOB, LiFSI, LiODFB or LiNO3; (5) The second lithium salt includes at least one of LiTFSI, LiPF6, LiBF4, LiBOB, LiFSI, LiODFB or LiNO3; (6) The mass ratio of the first polymer, the second polymer, the first lithium salt, and the first oxide solid electrolyte is (20-30): (5-10): (20-30): (30-40); (7) The mass ratio of the third polymer, the second lithium salt, and the second oxide solid electrolyte is (20-35):(10-20):(40-60).

5. The solid-state battery according to claim 1, characterized in that: The particle size of the first oxide solid electrolyte in the first composite polymer electrolyte presents a gradient distribution, and the particle size of the first oxide solid electrolyte presents a decreasing trend along the direction close to the positive electrode; and / or, The concentration of the first oxide solid electrolyte in the first composite polymer electrolyte presents a gradient distribution, and the concentration of the first oxide solid electrolyte presents a decreasing trend along the direction close to the positive electrode; and / or, The particle size of the second oxide solid electrolyte in the second composite polymer electrolyte presents a gradient distribution, and the particle size of the second oxide solid electrolyte presents an increasing trend along the direction close to the negative electrode; and / or, The concentration of the second oxide solid electrolyte in the second composite polymer electrolyte presents a gradient distribution, and the concentration of the second oxide solid electrolyte presents an increasing trend along a direction approaching the negative electrode.

6. The solid-state battery according to claim 1, characterized in that: The first solid electrolyte layer further includes a first plasticizer, the second solid electrolyte layer further includes a second plasticizer, and the first solid electrolyte layer and the second solid electrolyte layer satisfy at least one of the following features (1) to (4): (1) The first plasticizer includes at least one of dimethyl carbonate, ethyl methyl carbonate or propylene carbonate; (2) The mass fraction of the first plasticizer in the first solid electrolyte layer is 1% to 2%; (3) the second plasticizer comprises at least one of dimethyl carbonate, ethyl methyl carbonate or propylene carbonate; (4) The mass fraction of the second plasticizer in the second solid electrolyte layer is 1% to 2%.

7. The solid-state battery according to any one of claims 1 to 6, characterized in that: The thickness of the first solid electrolyte layer is A, the thickness of the second solid electrolyte layer is B, and A and B satisfy: 4 / 10≤A / (A+B)≤6 / 10; and / or, 5μm≤A+B≤30μm.

8. A method for preparing a solid-state battery, characterized in that: The following steps are involved: S1, mixing a raw material for preparing a first polymer solid electrolyte and a first active filler to obtain a first mixed solution, and subjecting the first mixed solution to a cross-linking polymerization reaction to obtain a first solid electrolyte layer, wherein the first active filler includes a first oxide solid electrolyte; S2, mixing a raw material for preparing a second polymer solid electrolyte and a second active filler to obtain a second mixed solution, and subjecting the second mixed solution to an in-situ polymerization reaction to obtain a second solid electrolyte layer, wherein the second active filler includes a second oxide solid electrolyte; S3, compounding the first solid electrolyte layer and the second solid electrolyte layer to obtain a composite solid electrolyte membrane; S4. Place the composite solid electrolyte membrane between the positive electrode and the negative electrode, with the first solid electrolyte layer close to the positive electrode and the second solid electrolyte layer close to the negative electrode, to obtain a solid-state battery.

9. The method for preparing a solid-state battery according to claim 8, characterized in that: In step S1, the mixing of the raw material for preparing the first polymer solid electrolyte and the first active filler comprises: firstly mixing the first polymer and the first solvent evenly, then adding the second polymer, the photoinitiator and the first lithium salt, mixing evenly to obtain a first intermediate mixed solution, and mixing the first intermediate mixed solution with the first active filler to obtain the first mixed solution; and / or, In step S1, the cross-linking polymerization reaction is carried out under the action of a photoinitiator and under the irradiation of ultraviolet light; and / or, In step S2, mixing the raw material for preparing the second polymer solid electrolyte with the second active filler includes: mixing the second active filler with a dispersant and a second solvent, and then adding a second lithium salt and a monomer for forming a third polymer to obtain the second mixed solution.

10. The method for preparing a solid-state battery according to claim 9, characterized in that: The first solvent comprises at least one of N,N-dimethylformamide, N-methylpyrrolidone or polyethylene glycol; and / or, The second solvent comprises at least one of N,N-dimethylformamide, N-methylpyrrolidone or polyethylene glycol; and / or, The dispersant comprises alcohols; and / or, The second mixed solution further contains an initiator, and the initiator includes azobisisobutyronitrile; and / or, The intensity of the ultraviolet light is 220 mW / cm 2 Up to 230mW / cm 2 within the scope of and / or, The conditions of the in-situ polymerization reaction include: temperature of 70° C. to 100° C., time of 20 min to 60 min, and rotation speed of 300 r / min to 1000 r / min.

Citation Information

Patent Citations

  • A two-layer or multi-layer polymer electrolyte and a battery

    CN108963334A

  • Polymeric solid electrolyte and lithium secondary battery comprising same

    CN110100346A

  • Hybrid solid state electrolyte for lithium secondary battery

    CN110268573A

  • Composite solid electrolyte and preparation method thereof and all-solid-state lithium ion battery containing composite solid electrolyte

    CN110729513A

  • Asymmetric solid electrolyte, preparation method thereof and application thereof in high-voltage solid-state battery

    CN111276738A